Dispositional Flow and Performance in Brazilian Triathletes - Garcia, William Fernando; Codonhato, Renan; Mizoguchi, Marcus Vinicius; do Nascimento Junior, José Roberto Andrade; Aizava, Paulo Vitor Suto; Ribas, Marcelen Lopes; Caruzzo, Aryelle Malheiros; Vissoci, João Ricardo Nickenig; Fiorese, Lenamar (Frontiers in Psychology, 2019)
Flow is a mental state characterized by total immersion and focus in an activity; performing it pleasurably. Such a state is considered optimal for performance. The present study analyzed the relationship between dispositional flow and performance in triathletes. The sample consisted of 328 athletes (294 males and 34 females; mean age of 37.42 ± 7.18 years) competing in the Ironman Brazil – Florianópolis – South American Championship 2017. Instruments were an identification sheet, the Dispositional Flow Scale (DFS-2) and athletes’ total race times. Data were analyzed using R, through the Shapiro–Wilk normality test, Mann–Whitney’s U, Spearman Correlation, and Network Analysis [Least Absolute Shrinkage and Selection Operator (LASSO)], using strength, closeness, and betweenness as centrality measurements. Results show a positive correlation between age and practice time (r = 0.34), inverse relationship between practice time and total race time (r = −0.25), and inverse correlations between race time and 05 of the 09 flow dimensions (r between −0.17 and −0.11), suggesting better performances were related to more practice time and higher disposition to flow. Flow conditions, flow characteristics, individual characteristics, and performance were separately grouped in the network structure. Challenge–skill balance was the most influential node, with the highest closeness and betweenness values; challenge–skill balance, clear goals, control, and action-awareness merge directly influenced better race times. Sample’s top 50 performers had significantly higher disposition to challenge-skill balance, clear goals, control and feedback. Practical implications of flow mechanisms are discussed. Dispositional flow was positively related to objective performance in Brazilian triathletes.